Appendix 2: Major Differences between Old Church Slavonic and Old Rusian - Nesset, Tore (Septentrio Educational, 2015)
This appendix gives you a brief overview of the major differences between Old Church Slavonic and Old Rusian. This is obviously useful when you are working with Old Church Slavonic texts, but it also enables you to identify slavonicisms (Church Slavic elements) in Old Rusian and Modern Russian texts. For more information and examples, see Galinskaja (1997: 6–8).